2015
DOI: 10.1080/00981389.2015.1059398
|View full text |Cite
|
Sign up to set email alerts
|

Framing Effects on End-of-Life Preferences Among Latino Elders

Abstract: This study compared how the presentation of end-of-life (EOL) choices influences responses by Latino and White older adults relative to resuscitation preferences. The authors apply prospect theory, which deals with decision making based on how choices are framed. Participants were presented with differently ordered questions framing a resuscitation scenario and asked to rate their preferences. Results show that Latino participants were significantly influenced by the framing order of treatment options with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We stratified data according to study type (i.e., qualitative, quantitative, mixed methods observation, interventional) using standard extraction templates in Excel and Access datasheets. Data were extracted and assigned to the following categories: Study reference (i.e., first author, year of publication, country of study origin); Study aim; Study setting; Sample size; Population characteristics (e.g., age, sex, definition of multimorbidity, patient prognosis or illness severity, cancer or non-malignant condition); Preference assessment method (e.g., interview or questionnaire); Context of preference (i.e., hypothetical/real, preference-sensitive situation); Information provided by the authors on the presentation of alternatives (e.g., positive or negative framing [16,17]); Description of phenomenon of interest (EoL care elements that patients were asked about, e.g., resuscitation preference); Results of described phenomenon of interest (e.g., proportion of participants expressing a preference for a specific type of EoL care).…”
Section: Data Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…We stratified data according to study type (i.e., qualitative, quantitative, mixed methods observation, interventional) using standard extraction templates in Excel and Access datasheets. Data were extracted and assigned to the following categories: Study reference (i.e., first author, year of publication, country of study origin); Study aim; Study setting; Sample size; Population characteristics (e.g., age, sex, definition of multimorbidity, patient prognosis or illness severity, cancer or non-malignant condition); Preference assessment method (e.g., interview or questionnaire); Context of preference (i.e., hypothetical/real, preference-sensitive situation); Information provided by the authors on the presentation of alternatives (e.g., positive or negative framing [16,17]); Description of phenomenon of interest (EoL care elements that patients were asked about, e.g., resuscitation preference); Results of described phenomenon of interest (e.g., proportion of participants expressing a preference for a specific type of EoL care).…”
Section: Data Itemsmentioning
confidence: 99%
“…Studies were categorized according to study design, whereby the assessment depended on the employed methodology. The tool was adapted to include a column evaluating the existence of a framing effect, which is a cognitive bias that occurs when the way information is presented influences the choices patients make [16,17]. The framing effect was independently assessed by two review authors (A.I.G.-G., M.-S.B.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Sixteen studies were conducted in community-based settings [ 18 33 ], eight in out-patient clinical care units (i.e., dialysis centres, cancer clinics, HIV clinic) [ 34 41 ], seven in urban hospitals [ 42 48 ] and six in primary care settings [ 49 54 ]. Eleven studies focused on a multi-racial/ethnic population [ 20 , 30 , 37 , 42 , 45 49 , 51 , 53 ]; 10 on patients of Latino descent [ 23 , 26 , 27 , 34 , 36 , 39 , 44 , 50 , 52 , 54 ] and African American descent [ 18 , 19 , 21 , 24 , 32 , 35 , 38 , 40 , 41 , 43 ]; two on patients of Chinese American descent [ 22 , 25 ]; and one on patients of Chinese Australian [ 33 ], Korean American [ 28 ], South Asian Indian American [ 29 ] and Asian American descent [ 31 ]. Study characteristics can be found in S1 Table .…”
Section: Resultsmentioning
confidence: 99%
“…[ 21 , 22 , 24 , 26 29 , 31 , 32 , 35 , 38 , 40 , 41 , 45 , 46 ]; healthcare provider-led interventions (i.e., palliative care consults, patient navigators, lay health workers, etc.) [ 34 , 37 , 42 44 , 47 49 ]; educational tools (i.e., videos, booklets) [ 18 20 , 25 , 33 , 53 , 54 ]; paper-based and electronic decision aids [ 30 , 50 52 ]; and communication strategies [ 23 , 36 , 39 ]. Twenty-seven tools were aimed at supporting patients [ 7 , 21 , 23 27 , 29 , 31 34 , 36 39 , 42 48 , 50 53 ]; five at supporting family members [ 18 20 , 28 , 30 ]; four at supporting both patients and families [ 35 , 40 , 41...…”
Section: Resultsmentioning
confidence: 99%
“… 14 16 More specifically to ACP, BE research has shown that the way questions and information are framed to patients in EOL decision-making can impact their preferences and choices. 17 , 18 Studies have also explored other cognitive barriers to ACP uptake, and the potential for the use of behavioural theories in EOL care decision-making. 19 , 20 In fact, simply being aware of potential behavioural biases can assist patient’s ability to revise counterproductive beliefs in the ACP decision process.…”
Section: Introductionmentioning
confidence: 99%